Study on acoustic reflection characteristics of layered sea ice based on boundary condition method. Issue 6 (2nd November 2021) - Chen, Wenjian; Hu, Siwei; Wang, Yizhe; Yin, Jingwei; Korochensev, V.I.; Zhang, Yuxiang
Abstract : According to the boundary conditions between two adjacent layers, a method for calculating the acoustic reflection coefficient of the layered ice-snow model is proposed, which is called the boundary condition method (BCM). Based on the actual ice parameters chosen from Schwarz and Weeks data, reflection coefficients under different conditions are analyzed. Comparing the BCM with the impedance transfer method (ITM), the results verified the validity of the BCM. After calculating and analyzing the multilayer ice-snow, it can be found that snow layer has more influence on the low-frequency sound waves. Snow layers have varying effects on the sound reflection coefficient depending on ice thickness: the thicker the ice layer is, the less influence the snow layer has on the sound reflection coefficient. The ice reflection coefficient model is combined with the Bellhop sound field simulation model, and the sound field simulation results are compared with the ninth Chinese polar scientific expedition results.